Social implications of service e-learning in primary education - Mikelić Preradović, Nives (Array, 2012)
This paper presents a case study of service e- Learning project of developing an educational corner for the elementary school. Our main objective was to develop the educational corner that would help the elementary school and its teachers to provide their pupils with greater opportunities for learning through interesting educational activities. Our second goal was to motivate the primary education teachers to realize the importance of communication with their pupils in an online environment and to encourage them to place their educational materials online in order to establish better communication and interaction with their pupils. Our third goal was to make our students of information sciences to practically use knowledge and skills acquired through their studies while meeting the demands of global and diverse educational marketplace. Finally, the study's findings have implications for structuring effective service e-Learning projects to promote student learning, increase student civic engagement and establish successful collaboration with the institution of primary education.